Fluoride in Water Intake and Prevalence of Dental Fluorosis Stains among Children in Central Benin - Avocefohoun, Alphonse S.; GBAGUIDI, AHOTONDJI BERTIN; SINA, HAZIZ; BIAOU, OLIVIER; HOUNSOU, Christophe S.; BABA-MOUSSA, LAMINE (My University, 2017)
Dental fluorosis is caused by excessive uptake of fluoride, characterized by brown enamel mottling that starts with white spots, while bones and virtually every organ can be affected by well-known anti-thyroid characteristics of the flourine. The aim of our work, was to establish the relationship between the consumption of fluoride-rich water and the prevalence of dental fluorosis in school children aged between 6 and 12 years old in Djidja (Benin). Methods: An investigation of fluorosis case-finding was conducted by a dentist and water points near the schools were collected to determine their fluoride concentration. Results: A prevalence of 20.53% (115 over 560 school children sample) were reported to have severe dental fluorosis, a. The fluorine content analysis of the water sample collected from the seven.water points close to each school or residence in the target population revealed an average fluoride ion content of 2.20 mg/L in the drinking water of schoolchildren in the study area. The values vary from 1.51 mg/L to 3.02 mg/L and largely higher than the recommendations of WHO (0.7 mg/L to 1.2 mg/L). From this study, it should be remembered that fluorosis does not vary with sex. The highest frequencies are obtained with schoolchildren in the 8 to 11 age group, and fluorine water levels vary from place to place. These results are in fact consistent with the results of a good number of authors. In addition, body surfaces between 1501 and 1520 have the highest prevalence of dental fluorosis in our study population. It is therefore urgent to treat these waters in order to reverse the thorny public health problem of dental fluorosis.
Keywords: Dental fluorosis; Prevalence; Water; Grade; Fluoride; School children